ANALISIS POLA PENDAPATAN RUMAH TANGGA PERTANIAN PRA DAN PASCA TERJADINYA KRISIS EKONOMI DI INDONESIA: APLIKASI MULTIPLIER DECOMPOSITION PADA SISTEM NERACA SOSIAL - Firmansyah Firmansyah (Muhammadiyah University Press, 2004)
Contraction of Indonesia's production sectors in 1998 as economic crisis impacts, have not been occurred on Farm, Livestock, Forestry and Fisheries sector and Electricity, Gas and Water sector. Particularly on Farm, Livestock, Forestry and Fisheries sector is interesting that the sector have been gave a second big contribution on Indonesia GDP less than Manufacturing sector, meanwhile most Indonesia citizen are farmer. On the other word, this sector is the Indonesia economy base.We have not said yet that Indonesia's citizen as prosperous as before crisis. Because, nor the sector it self and its agents would not live 'alone' and need others sector's commodities. It could be said, that linkage with the other sectors is high.The aim of this is to observe the agricultural household income, pre and post economic crisis, that we have used Indonesia SAM table 1995, 1998 and 1999 and multiplier decomposition analysis.Analysis result of SAM table explains a big shock of economic activity on agricultural household particularly on farm workers household and farmer landowner 0-0,5 Ha households. Although on 1998 agricultural household is worse than condition before, the prospect of recovery has been seen on income condition and agricultural household expenditure on SAM 1999 observation.Multiplier analysis on SAM table indicate that from 1995 to 1999 the sock of economic activities by agricultural household less than non-agricultural household. In fact, economic crisis did not give significant impact on agricultural household, however the recovery of agricultural household is sluggish. The result shows that from 1995 to 1999 agricultural household is consistent, mainly on farmer land owner 0-0,5 Ha household and farmer worker household.